Muscle development of livestock animals [ physiology, genetics and meat quality - Everts, M. E.; Haagsman, H. P.; Pas, Marinus F. W. te (CABI, 2004)
Well-developed and functional muscle tissues are a prerequisite for healthy meat-producing animals. Good muscle development leads to improved meat quality. Hence modern breeds of livestock animal have been selectively bred for better conformation, incresed muscle size and increased muscle-to-bone ratio. This book describes all aspects of muscle development research, and contains contributions from leading research groups around the world.